2021
DOI: 10.1002/mmce.23036
|View full text |Cite
|
Sign up to set email alerts
|

Quantum near field probe for integrated circuits electromagnetic interference at wafer level

Abstract: With the complexity and integration of integrated chips increasing, existing integrated circuits electromagnetic interference techniques using metallic probes cannot meet the emerging demand at single die level or wafer level, which requires micron spatial resolution and ultraweak invasiveness. In this article, we developed a non-invasive near field probe in the fiber format using nitrogen-vacancy center in diamond, which was attached to the tip of fiber as microwave B-field sensing element. Subsequently, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Once excited, the NV center generates 637 nm red fluorescence, which returns along the same light path, but passes through the dichroic mirror to get focused in the receiving area of SPCM. It is worth mentioning that in the fabrication of fiber probes, we detected the fluorescence intensity by spectroscopy and found that the thinning of the fiber ends could significantly enhance the fluorescence 10 . The fiber probe is therefore specially tapered to improve the efficiency of fluorescence collection, leading to the suppression of photon shot noise 18 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once excited, the NV center generates 637 nm red fluorescence, which returns along the same light path, but passes through the dichroic mirror to get focused in the receiving area of SPCM. It is worth mentioning that in the fabrication of fiber probes, we detected the fluorescence intensity by spectroscopy and found that the thinning of the fiber ends could significantly enhance the fluorescence 10 . The fiber probe is therefore specially tapered to improve the efficiency of fluorescence collection, leading to the suppression of photon shot noise 18 .…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that in the fabrication of fiber probes, we detected the fluorescence intensity by spectroscopy and found that the thinning of the fiber ends could significantly enhance the fluorescence. 10 The fiber probe is therefore specially tapered to improve the efficiency of fluorescence collection, leading to the suppression of photon shot noise. 18 In addition, the optical module is designed to eliminate the interference of miscellaneous light.…”
Section: Imaging Principlementioning
confidence: 99%
See 2 more Smart Citations
“…6 We developed a magnetic current imaging (MCI) technique at microwave frequency in this work. The current density is linearly proportional to the surface Hfield of the chip 7,8 which is sensed by a fiber quantum probe, a diamond crystal containing nitrogen-vacancy (NV) center attached to the tip of a tapered fiber. This probe is an essential extension of the commercial nearfield H-probe, which is metallic, bringing some distortion to the electromagnetic field of the chip under test.…”
Section: Introductionmentioning
confidence: 99%